COMPARISON OF MOTIVATION TO LEARN ISLAMIC RELIGIOUS EDUCATION IN BOARDING AND NON-BOARDING STUDENTS IN SCHOOLS - Fitri Balqis Khusnul Khotimah; Mukhsin Mukhsin; Ilzam Hubby Dzikrillah Alfani; Muhammad Azmi Auf; Muhammad Fahmi Shihab (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to determine the differences in Islamic Religious Education learning motivation between boarding students and non-boarding students, as well as the extent of these motivational differences. The research employed a quantitative approach using a comparative method. The population consists of 60 students at Darul Hikmah Mataram Junior High School, with the entire population included as the sample. Data was collected using a questionnaire based on a 5-point Likert scale. The findings revealed a significant difference in PAI learning motivation between boarding and non-boarding students. This conclusion was supported by an independent sample t-test using SPSS 27, which yielded a significance value of 0.004. Since the significance value was <0.05, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. The implication of this research was that boarding school environments may provide more conducive conditions for enhancing students’ learning motivation, especially in religious education, through structured routines, stronger peer interactions, and closer academic supervision. These insights can guide educators and policymakers in developing strategies to improve learning motivation both within and outside boarding school systems.